The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0101-31222007000300023
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de genótipos de soja em semeadura de inverno, em Selvíria, MS: produção e qualidade fisiológica de sementes

Abstract: RESUMO -A semeadura da soja fora do período convencional tem se tornado uma opção para produção de sementes com elevado potencial fisiológico, o que torna necessária a busca por materiais adaptados às novas condições ambientais, fornecendo, assim, maiores subsídios aos agricultores. A pesquisa teve por objetivo identificar genótipos capazes de produzir sementes de alta qualidade no inverno, em Selvíria, MS. /1998 e avaliadas quanto às características agronômicas e o potencial fisiológico das sementes. O deline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
1
0
4
Order By: Relevance
“…This fact can be explained by the climatic conditions prevailing in the seed filling and maturation stages, in which the occurrence of frost (07/18/17 and 07/19/17) negatively affected the germination of seeds from this period. These results are in agreement with those found by Meotti et al (2005) and Silva, Lazarini, and Sá (2007), who observed that both anticipation and delay in the sowing date were detrimental to obtaining soybean seeds with higher physiological quality. The variability in the expression of the physiological potential of seeds of species subject to variation in the sowing season, as well as chia, due to the response to the photoperiod, is described in others studies (Albrecht et al, 2008;Viganó et al 2010).…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 93%
See 1 more Smart Citation
“…This fact can be explained by the climatic conditions prevailing in the seed filling and maturation stages, in which the occurrence of frost (07/18/17 and 07/19/17) negatively affected the germination of seeds from this period. These results are in agreement with those found by Meotti et al (2005) and Silva, Lazarini, and Sá (2007), who observed that both anticipation and delay in the sowing date were detrimental to obtaining soybean seeds with higher physiological quality. The variability in the expression of the physiological potential of seeds of species subject to variation in the sowing season, as well as chia, due to the response to the photoperiod, is described in others studies (Albrecht et al, 2008;Viganó et al 2010).…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 93%
“…The environmental conditions during maturation and harvesting of chia plants favored the maintenance of seed vigor at all the sowing dates studied. In a paper on the physiological quality of soybean seeds of Silva, Lazarini and Sá (2007), both anticipation and delay in the sowing date were detrimental to obtaining seeds with higher physiological quality because the seeds did not tolerate temperature stress and high relative humidity demonstrated by the aging test. For the western region of Santa Catarina Stage, Brazil, sowing in the middle of December (15/12) is recommended for the production of soybean seeds with high vigor (Bornhofen et al, 2015).…”
Section: Journal Of Agricultural Sciencementioning
confidence: 99%
“…Desempenho semelhante foi encontrado por Silva et al (2007) em 32 cultivares de soja, entre elas IAC-19, Conquista e IAC 8-2 semeadas na mesma região e época.…”
Section: Resultsunclassified
“…Assim as sementes produzidas apresentam potencial fisiológico e qualidade sanitária superiores como foram comprovados por diversos pesquisadores (Marcos Filho et al, 1984;Tragnago e Bonetti, 1984;Nakagawa et al, 1986;Medina et al, 1997;Braccini et al, 2003;Silva et al, 2007).…”
Section: Introductionunclassified
“…Estes resultados estão de acordo aos encontrados por CRUSCIOL et al (2002), em que detectou maior percentual de plântulas normais no teste de envelhecimento acelerado quando foi usado o sistema de irrigação por aspersão. Nos resultados obtidos por SILVA et al (2007), as sementes de soja das cultivares Conquista e IAC 8-2 produzidas em área sem suplementação hídrica obtiveram valores de 84 e 95% no teste de envelhecimento acelerado. DORNBOS et al (1989), constatou que em sementes de soja são relatadas ocorrências de redução da germinação e do vigor como consequência da deficiência hídrica.…”
Section: Resultsunclassified